Influence of internal parameters on the signal value in optical sensor based on the non-ideal heterostructure CdS-Cu₂S - Borschak, V.A.; Brytavskyi, Ie.V.; Smyntyna, V.A.; Lepikh, Ya.I.; Balaban, A.P.; Zatovskaya, N.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
The signal (defined by conductivity) of optical sensor based on CdS-Cu₂S
heterostructure both at direct and alternative current strongly depends on barrier
parameters that can change under exposure. It was stated that such parameter as
resistance of space charge region considerably depends on its width at a constant barrier
height, and this dependence is similar to linear shape. This behavior can indicate
domination of tunnel multistep mechanisms in the studied structure, for instance, the
mechanism of tunnel-jumping conductivity.